Iklim Psikologis sebagai Prediktor Kesejahteraan Psikologis pada Karyawan Industri Farmasi di Jabodetabek - Chuhendra Ayu Setya Yuntari; Dina Syakina; Nur Zaskia Rahmayanti; Reno Laila Fitria; Holy Greata Singadimeja (Empathy : Jurnal Fakultas Psikologi, 2021)
Psychological Climate as a Predictor of Psychological Well-Being for Pharmaceutical Industry Employees in JabodetabekThis study aims to analyze the relationship between psychological climate and psychological well-being of pharmaceutical industry employees in the Greater Jakarta area. Psychological well-being is defined as a state where employees of the pharmaceutical industry do not experience anxiety, anxiety, depression, and various other psychological disorders. This research was conducted using a quantitative correlational study with 176 respondents, using the Psychological Well-Being Scale (PSWBS) to measure psychological well-being and the Psychological Climate Scale (PCS) to measure psychological climate. Data analysis was performed using simple regression analysis to test the hypothesis. The results of the study found that there was a positive relationship between psychological climate and psychological well-being of pharmaceutical industry employees. With the influence of a psychological climate of 4.00% on psychological well-being, younger employees tend to have higher psychological well-being than older employees.